Lamotrigine pharmacokinetic/pharmacodynamic modelling in rats - Castel-Branco, M. M. (2005)
The aim of this study was to perform a pharmacokinetic/pharmacodynamic (PK/PD) modelling of lamotrigine following its acute administration to rats. Adult male Wistar rats were given 10 mg/kg of lamotrigine intraperitoneally. Plasma and brain samples were obtained at predetermined times over 120 h post-dose and analysed by liquid chromatography. The anticonvulsant profile against maximal electroshock seizure stimulation was determined over 48 h after dosing. As a linear relationship between lamotrigine plasma and brain profiles was observed, only the plasma data set was used to establish the PK/PD relationship. To fit the effect–time course of lamotrigine, the PK/PD simultaneous fitting link model was used: the pharmacokinetic parameters and dosing information were used in the one-compartment first-order model to predict concentrations, which were then used to model the pharmacodynamic data with the sigmoid Emax model, in order to estimate all the parameters simultaneously. The following parameters were obtained: Vd ¼ 2.00 L/kg, kabs ¼ 8.50 h)1, kel ¼ 0.025 h)1, ke0 ¼ 3.75 h)1, Emax ¼ 100.0% (fixed), EC50 ¼ 3.44 mg/L and c ¼ 8.64. From these results, it can be stated that lamotrigine is extensively distributed through the body, its plasma elimination half-life is around 28 h and a lamotrigine plasma concentration of 3.44 mg/L is enough to protect 50% of the animals. When compared with humans, the plasma concentrations achieved with this dose were within the therapeutic concentration range that had been proposed for epileptic patients. With the present PK/PD modelling it was possible to fit simultaneously the time-courses of the plasma levels and the anticonvulsant effect of lamotrigine, providing information not only about the pharmacokinetics of lamotrigine in the rat but also about its anticonvulsant response over time. As this approach can be easily applied to other drugs, it becomes a useful tool for an explanatory comparison between lamotrigine and other antiepileptic drugs.